Short‐ or long‐term high‐fat diet feeding plus acute ethanol binge synergistically induce acute liver injury in mice: An important role for CXCL1. Issue 4 (3rd July 2015) - Chang, Binxia; Xu, Ming‐Jiang; Zhou, Zhou; Cai, Yan; Li, Man; Wang, Wei; Feng, Dechun; Bertola, Adeline; Wang, Hua; Kunos, George; Gao, Bin
<x xml:space="preserve">Abstract</x> Obesity and alcohol consumption often coexist and work synergistically to promote steatohepatitis; however, the underlying mechanisms remain obscure. Here, we demonstrate that feeding mice a high‐fat diet (HFD) for as little as 3 days markedly exacerbated acute ethanol binge–induced liver neutrophil infiltration and injury. Feeding mice with an HFD for 3 months plus a single binge of ethanol induced much more severe steatohepatitis. Moreover, 3‐day or 3‐month HFD‐plus‐ethanol binge (3d‐HFD+ethanol or 3m‐HFD+ethanol) treatment markedly up‐regulated the hepatic expression of several chemokines, including chemokine (C‐X‐C motif) ligand 1 (Cxcl1), which showed the highest fold (approximately 20‐fold and 35‐fold, respectively) induction. Serum CXCL1 protein levels were also markedly elevated after the HFD+ethanol treatment. Blockade of CXCL1 with a CXCL1 neutralizing antibody or genetic deletion of the Cxcl1 gene reduced the HFD+ethanol‐induced hepatic neutrophil infiltration and injury, whereas overexpression of Cxcl1 exacerbated steatohepatitis in HFD‐fed mice. Furthermore, expression of Cxcl1 messenger RNA was up‐regulated in hepatocytes, hepatic stellate cells, and endothelial cells isolated from HFD+ethanol‐fed mice compared to mice that were only given the HFD, with the highest fold induction observed in hepatocytes. In vitro stimulation of hepatocytes with palmitic acid up‐regulated the expression of Cxcl1 messenger RNA, and this up‐regulation was attenuated after treatment with an inhibitor of extracellular signal–regulated kinase 1/2, c‐Jun N‐terminal kinase, or nuclear factor κB. In addition, hepatic or serum levels of free fatty acids were higher in HFD+ethanol‐fed mice than in the control groups. Conclusion: An HFD combined with acute ethanol consumption synergistically induces acute liver inflammation and injury through the elevation of hepatic or serum free fatty acids and subsequent up‐regulation of hepatic CXCL1 expression and promotion of hepatic neutrophil infiltration. (Hepatology 2015;62:1070‐1085)